Randomized Control Trial on the Effectiveness of Collagen Cross-linking on Bullous Keratopathy. Issue 11 (November 2020) - Choy, Bonnie Nga Kwan; Ng, Alex Lap Ki; Zhu, Ming Ming; Liu, Catherine Chunling; Xu, Sheng; Lai, Jimmy Shiu Ming
Abstract : Purpose: To investigate the long-term effect and safety of collagen cross-linking (CXL) on patients with bullous keratopathy (BK) in a randomized control manner. It is, to our knowledge, the first randomized control study on the effect of CXL on BK. Methods: Subjects were randomized to receive CXL as in the standard protocol for treating keratoconus or a placebo treatment. Subjects were assessed at baseline and up to 12 months after treatment. Primary outcomes were central corneal thickness (CCT) and pain scores. Results: Forty-two patients with BK participated in the study treatment, 26 subjects were randomized to the CXL group and 16 subjects to the control group. The reduction of CCT in the CXL group was 37.6 and 63.8 μm at 2 and 4 weeks, respectively, which were significantly higher than that in the control group. However, there was no statistical difference in CCT reduction between the 2 groups at 12 weeks and after. There were no consistent advantages in pain score, corneal clarity, and visual acuity over the controls throughout the 1-year follow-up. However, CXL was associated with more recurrent epithelial defect (12%), and 2 of the 3 subjects with epithelial defect required amniotic membrane transplant. Conclusions: CXL reduced corneal thickness in the patients with BK, at least for the initial period. However, there were no improvement in pain, corneal clarity, and vision that were of more clinical relevance to the patients. Its short-term benefit was unlikely to outweigh its potential risk of recurrent epithelial defect. Abstract : Supplemental Digital Content is Available in the Text.